2020
DOI: 10.1177/0143831x20904782
|View full text |Cite
|
Sign up to set email alerts
|

Re-inventing the self: Implications of trade union revitalization

Abstract: Although trade union revitalization processes have been thoroughly examined by industrial relations scholars, less is known about the implications of such processes on unions’ self-image. This article addresses that gap in knowledge by investigating how the self-image of a major Swedish public-sector trade union, the SKTF/Vision, changed after a thorough revitalization process took place. The findings indicate that due to pressure resulting from public-sector privatization, the union abandoned much of its form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Political campaigning not only demonstrates unions’ societal and political relevance, it also reveals the movement’s identity. Political positioning has been a crucial characteristic trait of the unions’ identities, and a clearly communicated identity has proven to be important for constructing successful unions in the past (Jansson, 2020a), as well as for contemporary unions engaged in revitalisation processes (Gasparri et al , 2019; Smale, 2020; Jansson, 2020b). Prior studies have shown that online political mobilisation is common among trade unions (Hodder and Houghton, 2015; Pasquier et al ., 2020), although little attention has been paid to mobilisation via such widespread platforms as YouTube.…”
Section: Discussionmentioning
confidence: 99%
“…Political campaigning not only demonstrates unions’ societal and political relevance, it also reveals the movement’s identity. Political positioning has been a crucial characteristic trait of the unions’ identities, and a clearly communicated identity has proven to be important for constructing successful unions in the past (Jansson, 2020a), as well as for contemporary unions engaged in revitalisation processes (Gasparri et al , 2019; Smale, 2020; Jansson, 2020b). Prior studies have shown that online political mobilisation is common among trade unions (Hodder and Houghton, 2015; Pasquier et al ., 2020), although little attention has been paid to mobilisation via such widespread platforms as YouTube.…”
Section: Discussionmentioning
confidence: 99%
“…Unionen has managed to reverse the trend of membership decline, while Vision has stopped its decline. Within Vision, awareness of the need for image management was clear: the chairperson of Vision actually described the old organization as 'grey, old-mannish and outof-date' and as therefore needing a remake, including a name change (Jansson 2019).…”
Section: Selection Of Casesmentioning
confidence: 99%
“…Refraining from defining a union in terms of specific values or ideologies makes it possible to recruit members with very different ideological positions; therefore, this may be the most successful route to organizing the middle class. Historically, both Unionen and Vision have had narrower membership bases and more pronounced values than displayed in their YouTube videos (Jansson 2019). As structural changes decrease the size of the working class and blurring the line between the workers and the white-collar workers, it is possible that the organizational traits displayed by Vision and Unionen will become more common in future.…”
mentioning
confidence: 99%